Caspase-6 is a Dispensable Enabler of Adult Mammalian Axonal Degeneration. (10th February 2018) - Woo, V.; Cheng, C.; Duraikannu, A.; Chandrasekhar, A.; Purdy, K.; Martinez, J.A.; Zochodne, D.W.
Highlights: Caspase-6 is expressed during early axonal degeneration, including within terminals of skin axons. Cutaneous capsaicin generates a cutaneous axonopathy serially visualized in live mouse ear pinna thy-1 YFP axons. Caspase-6 inhibition or knockdown were associated with a mild delay in the development of axonopathy. Capsase-6 inhibition inhibited axon fragmentation in vitro and ex vivo. Capsase-6 null mice experienced mild delays in the development of axonal degeneration in vivo . Abstract: The progress of axonal degeneration (AxD) following injury or insult impacts both recovery from axonal transection and protection of axons from diverse insults, or axonopathy. Here we provide evidence that increases in capase-6 (Casp6) expression and action contribute to the progression of AxD. The expression of Casp6 protein and mRNA in distal branches of sensory axons undergoing AxD was confirmed. We developed and utilized a new model of axonopathy in live mice by serially visualizing the viability of cutaneous axons in the ear pinna that expressed an axonal YFP transgene, in response to capasaicin-induced AxD. Both specific pharmacological inhibition of caspase-6 and local knockdown offered early but subtle and mild attenuation of axonopathy. To evaluate an axon autonomous role of Casp6, we examined axon integrity following transection ex vivo, and analyzed the serial morphological fragmentation of neurofilament expression as a structural index of AxD. Adding a specific Casp6 inhibitor to the preparation delayed neurofilament fragmentation. Intact motor axons of Casp6 null mice had normal electrophysiological properties but, as tested serially during AxD, there was attenuated loss of excitability. Following transection, morphological features of AxD were evident in both wild type and Casp6−/− mice but the latter had evidence of slowed progression. Taken together, our findings suggest a subtle but dispensable enabling role of local Casp6 expression in axons undergoing AxD. Serial analysis of cutaneous ear pinna axons in live mice provides a useful and novel model of axonal integrity.